ChemInform Abstract: Synthesis of Functionalized 3‐Bromoindenes via Pd(II)‐Catalyzed Tandem Reactions of o‐(Alkynyl)styrenes: Taking Dioxygen as Sole Oxidant. Issue 25 (June 2016) - Zhou, Peng; Liu, Weibing; Qiu, Huihua
Abstract: Intramolecular Pd‐catalyzed cyclization of various o‐(alkynyl)styrenes includes bromopalladation/Heck cross‐coupling/β‐H elimination using oxygen as an oxidant affords 3‐bromoindenes of type (II).